PERAN TRISENTRA PENDIDIKAN DALAM OPTIMALISASI PROGRAM SEKOLAH RAMAH ANAK DI SDN 2 PANCOR - Abdul Hakim; Ahmad Yasar Ramdan; Dina Fadilah; Yul Alfian Hadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to analyze the role of the tri center of education family, school, and community in optimizing the implementation of the Child-Friendly School (CFS) program at SDN 2 Pancor. The study employed a qualitative method with a phenomenological approach. Data were collected through interviews, observations, and documentation involving the school principal, parents, and local community members. The findings reveal that the successful implementation of the child-friendly school program at SDN 2 Pancor is the result of strong synergy among the family, school, and community. Families play a vital role as the first and foremost educational environment, providing guidance, learning support, and instilling values of discipline and respect. Schools act as formal learning centers that create safe, comfortable, and inclusive environments through participatory learning and the provision of adequate facilities. Meanwhile, the community serves as a strategic partner by offering moral support, social engagement, and maintaining a healthy environment through joint activities, religious guidance, and community safety agreements around the school. Thus, collaboration among these three educational pillars has proven effective in creating a safe, enjoyable, and child-friendly learning climate. The results of this study are expected to serve as a reference for other schools in developing similar sustainable programs.